Design and Simulation for the Improvement of Cookies Packaging Process - Mohd Shahir; Mohd Rohisham, Mohamad Affan; Noor Azman, Noor Ezzat Nafie; Mat Hussin, Shakilla Nur Asimah; Wagiman, Abdullah; Mohamad, Mahmod Abdul Hakim (Multidisciplinary Applied Research and Innovation, 2020)
This project aims to enhance packaging timing in small scale industries which are usually home-based industries. In small scale food industries, food items need to be handled with care to ensure the quality of the food is not disturbed. We look towards a local food industry which is Pid’s Cookies based in Ampang, Selangor. We believe that we can produce a packaging system which is better and faster than the current system that they apply and our goal is to reduce the amount of workers needed and to further enhance the packaging system of these biscuits hence increasing the overall efficiency of the small scale industry. The fabrication of a biscuit packaging prototype requires metal that is safe for food items which is stainless steel and the fabrication process requires metal working processes such as cutting, joining, welding and bending. We used Solidworks 2019 to create the final outcome of our product and we also collect the data by using Solidworks simulation analysis as we can testify the strength of our product and do some analysis such as the strength of the support when some force exerted upon it. From the results, we can clearly see that how the construction of the model helps to understand each function of the parts. In conclusion, this product can be used by the small scale industry as we focus on the small scale industry that lack of resources to afford expensive packaging lines. We hope to produce an affordable packaging system to further enhance small local food industries. We also hope to fabricate a packaging system that is efficient and low cost while still maintaining the quality of the food.